(untitled) (Journal of Economic Research & Business Administration, 2016)
The article considers the peculiarities of the enterprise income and accounting income. Revenue from sales of finished goods and goods pur-chased and services is determined by the cost of implementation provided for in the agreement (contract) between the parties. In accounting, income is calculated as the difference between income and expenditure deter-mined in accordance with IFRS. Taxable income is the sum of the yield (loss) for the period determined in accordance with the tax laws. The tax regulations differ from the accounting requirements as a result there are differences in the definition of accounting income and taxable income. emporary or permanent differences may arise when the amendments due to changes in accounting policies or correction of fundamental errors made by adjusting the opening balance of retained earnings.